Aeromonas dhakensis: clinical isolates with high carbapenem resistance - Puah, Suat Moi (2023)
Aeromonas dhakensis is ubiquitous in aquatic habitats and can cause life-threatening septicaemia in humans. However, limited data are available on their antimicrobial susceptibility testing (AST) profiles. Hence, we aimed to examine their AST patterns using clinical (n = 94) and non-clinical (n = 23) isolates with dehydrated MicroScan microdilution. Carbapenem resistant isolates were further screened for genes related to carbapenem resistance using molecular assay. The isolates exhibited resistance to imipenem (76.9%), doripenem (62.4%), meropenem (41.9%), trimethoprim/sulfamethoxazole (11.1%), cefotaxime (8.5%), ceftazidime (6%), cefepime (1.7%) and aztreonam (0.9%), whereas all isolates were susceptible to amikacin. Clinical isolates showed significant association with resistance to doripenem, imipenem and meropenem compared to non-clinical isolates. These blacphA were detected in clinical isolates with resistance phenotypes: doripenem (67.2%, 45/67), imipenem (65.9%, 54/82) and meropenem (65.2%, 30/46). Our findings showed that the MicroScan microdilution method is suitable for the detection of carbapenem resistance in both clinical (48.9-87.2%) and non-clinical (4.3-13.0%) isolates. This study revealed that A. dhakensis isolates had relatively high carbapenem resistance, which may lead to potential treatment failure. Continued monitoring of aquatic sources with a larger sample size should be carried out to provide further insights.